2005
DOI: 10.1021/la051246q
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Dialysis Process for Liquid Crystalline Gel Formation

Abstract: The processes of gelation and liquid crystalline formation in the dialysis of Curdlan solution have been observed under crossed nicols, and the calcium concentration and pH of the inner solution were traced. The results showed that the gelation and the liquid crystalline formation occurred simultaneously to form liquid crystalline gel (LCG), but the birefringence of the LCG increased even after the gelation, suggesting further ordering of the Curdlan molecules. On the basis of the calcium ion diffusion, a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 10 publications
3
68
1
Order By: Relevance
“…The PBDT alignment in region I of the gel is further confirmed by small angle X-ray scattering measurements. 45 Our results show that the PBDT molecules align perpendicularly to the Ca 2 þ diffusion direction, which is opposite to the pattern reported for DNA and curdlan systems by Dobashi et al [51][52][53][54] However, we have noticed that their previous conclusion about the molecular orientation was not correct, and they have revised their conclusion in a recently published paper. 55 To track the diffusion-gelation process, we performed in situ observation of the entire gelation process under POM at different dialysis times (Figure 3a).…”
Section: Synthesis Of Physical Hydrogels With Centimeter-scale Anisotcontrasting
confidence: 98%
See 2 more Smart Citations
“…The PBDT alignment in region I of the gel is further confirmed by small angle X-ray scattering measurements. 45 Our results show that the PBDT molecules align perpendicularly to the Ca 2 þ diffusion direction, which is opposite to the pattern reported for DNA and curdlan systems by Dobashi et al [51][52][53][54] However, we have noticed that their previous conclusion about the molecular orientation was not correct, and they have revised their conclusion in a recently published paper. 55 To track the diffusion-gelation process, we performed in situ observation of the entire gelation process under POM at different dialysis times (Figure 3a).…”
Section: Synthesis Of Physical Hydrogels With Centimeter-scale Anisotcontrasting
confidence: 98%
“…They have claimed that the biomacromolecules orient along the cationic ions diffusion paths to form a radial structure. [52][53][54] We have found that PBDT, which has properties similar to those of biomacromolecules, is also capable of forming macroscopic anisotropic physical gels via a dialysis process. 40,45 In this process, a 1 wt% solution of PBDT with a Mw of 2.1 Â 10 6 g mol À1 and a C LC * of 2 was poured into a mold that consists of a pair of parallel glass plates separated by a 1-mm thick silicone spacer (Figure 2a).…”
Section: Synthesis Of Physical Hydrogels With Centimeter-scale Anisotmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerated cellulose hydrogel membranes are also strong enough to be used for dialysis in water. Dobashi and coworkers [25][26][27][28] successfully developed a facile dialysis method for fabricating physical biopolymer hydrogels with macroscopic ordered structures. Th ey immersed an aqueous solution of DNA or curdlan inside a semipermeable t ube in a multivalent cation solution, such as Ca 2+ and Co…”
Section: Structured Hydrogels With Biomacromolecular Assembliesmentioning
confidence: 99%
“…The experimental data for the gel growth process induced by dialysis are analyzed by a theory based on the following assumptions [4]. (a) All hydroxide anions flowing into the inner chitosan solution are used up to neutralize the solution.…”
Section: Survey Of Theorymentioning
confidence: 99%